Simulasi Pengendalian Persediaan Pupuk Menggunakan Metode Monte Carlo: Fertilizer Inventory Control Simulation Using the Monte Carlo Method - Okta Veza; Revi Illya Badri (Engineering and Technology International Journal, 2021)
Inventory simulation is not only an estimate of inventory but is an opportunity to adjust the actual and potential demand with the necessary marketing efforts, so that a benefit can be obtained from it, if the amount of inventory is too small (out of stock) and demand cannot If this is met, then this can lead to disappointment with customers and result in a loss of trust from customers. Meanwhile, if the amount of inventory is too much (over stock) it can also cause problems such as increased storage costs. An alternative solution to this problem is to use a Monte Carlo simulation which can measure or predict how much fertilizer should be provided, this simulation predicts sales in August and September so that The company can measure the amount of inventory in the month, with the first step determining the important variable, second Creating a cumulative probability distribution for each variable, third Assigning a random number interval for each variable, Generating random numbers with LCM (Linear Congruent Method), generating a series of experiments, simulations This study uses Ms. Excel in manual calculations and uses the Java programming language in the application of the system, it is concluded that the simulation results are close to the real state so that it is very suitable for forecasting fertilizer inventories at PT. Tazar Guna Mandir.